The advances in melanoma treatment - Pawlicki, Marek; Ziobro, Marek (Contemporary Oncology/Współczesna Onkologia, 2001)
Melanoma is a neoplasm with one of the highest increase in incidence. Treatment results were improved due to better diagnostic procedures and early treatment introduction in non-advanced melanoma cases. There is not any substantial improvementin the treatment of advanced melanoma. The review of recent papers dedicated to novel treatment method used in melanoma is the aim of this publication. New factors related to the clinical course of the disease were presented. Melastatin(MLSN-1) was described as very promisingprognostic factor for early stages of melanoma. Lack of expression of this gene is connected with increased risk of dissemination and decreased rate of overall survival. Overexpression of metaloproteins was presented as prognostic factor for locally advanced melanoma connected with poor prognostic. The recent studies suggested that decreased ability to apoptosis of melanoma cells is caused by lack of APAF-1 protein. The modulations of this protein level by drugs and gene therapy is considered. The role of the sentinel lymph node for the treatment choice and subsequent staging changes was discussed. There is a lack of randomised studies, which confirmed influence of this procedure on survival.The results of analyses of large database of melanoma patients revealed survival improvement of patients with micrometastases in regional lymph nodes compared t group with clinically involved lymph nodes. It caused that sentinel node biopsy is considered as staging procedure for patients entered into clinical studies and is taken into consideration in updated clinicla staging calssifications (TNM and AJCC). The recently closed trials with adjuvant treatment of patients with high risk of dissemination in melanoma patients were discussed. The survival improvement of patients treated with Interferon was proven in some of these trials. Optimal treatmenttiming as well as used doses are under investigation. The influence of new cytoxic drugs (fotemustin, temodal) on treatment schedule was presented. New approach for the liver metastasis with IL-2 combined with histamine derivative (ceplene) was discussed. Current investigations comparing efficacy/toxicity of DTIC, multidrug chemotherapy and biochemotherapy based on cytokines were summarised. There are not any statistically significant differences between these treatment modalities regarding overall survival. Multidrug Chemotherapy and biochemotherapy offer higher remission rate with increased treatment toxicity. Chemotherapy with DTIC is stimm considered as a standard treatment for patients out of the controlled clinical studies. Anticanacer vaccines are an alternative pathway in treatmentof melanoma but there are still in an early phase of clinical trials. The preliminary results did not revealed any substantial improvement in the treatment outcome.